Unbounded symmetric analytic functions on $\ell_1$ - Chernega, Iryna; Zagorodnyuk, Andriy (MATHEMATICA SCANDINAVICA, 2018)
We show that each $G$-analytic symmetric function on an open set of $\ell _1$ is analytic and construct an example of a symmetric analytic function on $\ell _1$ which is not of bounded type.